Ethereum Smart Contract Development in Solidity - Zheng, Gavin; Gao, Longxiang; Huang, Liqun; Guan, Jian.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
The general consensus is that BlockChain is the next disruptive technology, and Ethereum is the flagship product of BlockChain 2.0. However, coding and implementing business logic in a decentralized and transparent environment is fundamentally different from traditional programming and is emerging as a major challenge for developers. This book introduces readers to the Solidity language from scratch, together with case studies and examples. It also covers advanced topics and explains the working mechanism of smart contracts in depth. Further, it includes relevant examples that shed new light on the forefront of Solidity programming. In short, it equips readers with essential practical skills, allowing them to quickly catch up and start using Solidity programming. To gain the most from the book, readers should have already learned at least one object-oriented programming language.
Part 1. Preliminary -- Chapter 1. Basic Concepts -- Chapter 2. Preparation -- Part 2. Solidity Basics -- Chapter 3. Solidity Basics -- Chapter 4. Solidity Advanced Topics -- Part 3. Solidity Advanced Features -- Chapter 5. Application Binary Interface (ABI) -- Chapter 6. Operation Principles of Smart Contract -- Chapter 7. Upgradable Contract -- Chapter 8. Develop Secure Contract -- Chapter 9. Decentralized Application(DApp) -- Chapter 10. Debug -- Part 5. Prospect -- Chapter 11. Web Assembly (WASM).
Keywords: Application software; Computer programming; Programming languages (Electronic computers).; Coding theory; Information theory; Software engineering; Information Systems Applications (incl. Internet).; Programming Techniques; Programming Languages, Compilers, Interpreters; Coding and Information Theory; Software Engineering